The impact of psychosocial support and psychological well-being among expatriate students - Al-Ja'afreh, Somaya Abdel-Hameed; Al-krenawi, Alean; Al-Habies , Feras Ali; Abudoush, Ahmad Nabeel; Alourani , Omar Ismail Hamzeh (Journal of International Students, 2025)
This study explores the impact of a psychological and social support program on social support and psychological security among expatriate students. Using a quasi-experimental design, 48 Arab expatriate students at Al-Isra Private University (16 males, 32 females) were assigned to experimental and control groups (24 each). Standardized scales measured social support and psychological security before and after the intervention. Results showed moderate social support and low psychological security among students prior to the program. Post-intervention, the experimental group demonstrated statistically significant improvements (p < 0.05) in both areas, highlighting the program’s effectiveness. The study emphasizes the importance of ongoing psychological security assessments to enhance expatriates' mental well-being.